Revisiting the relationship between board structure and bank performance in Ethiopian commercial banks - Dereje Fedasa Hordofa (Cogent Business & Management, 2023)
This study examines the relationship between board structure and the performance of 15 Ethiopian commercial banks from 2010 to 2022. Using panel data analysis, the study assesses the impact of board size and gender diversity on performance, measured by return on equity (ROE) and net interest margin (NIM). The results indicate that board size does not significantly affect performance, while higher gender diversity is positively associated with higher ROE. Moreover, economic growth positively influences ROE, while remittances exhibit a negative correlation. After controlling for endogeneity, macroeconomic factors impact ROE but not NIM. The findings shed light on the complex governance-performance dynamics in developing banking systems, contributing valuable empirical evidence from multiple theoretical perspectives. The study suggests selective board size expansion and leveraging diversity. However, limitations include the exclusive focus on commercial banks and the relatively short timeframe. Overall, this analysis enhances our understanding of the study's focus on board structure-performance connections within the Ethiopian banking sector, emphasizing the need for context-specific research in this domain.
Keywords: 650; board structures; Ethiopia; fixed effects; panel model; performance of commercial banks; random effect